The Analysis of Productivity Growth of Tuber Crops in Nigeria (1995-2006) - L. T, Ogunniyi; A. O, Ajao (Asian Journal of Agriculture and Rural Development, 2012)
This study analyzed the productivity of Tuber crops in Nigeria from twenty states between the periods of 1995 -2006 using Data Envelopment Analysis (DEA) to estimate the total factor productivity (TFP) which was further decomposed to reveal the source of productivity growth over the reference period. Negative TFP growth was observed for all the tuber crops considered in the study on the average but an evidence of convergence in productivity level was observed when considering the starting TFP, majority of the states had low TFP (<0.6) but grew over the years by about 0.2 with Kaduna and Adamawa having the highest TFP for cocoyam and cassava respectively.